Czy prekariat zagraża spokojowi społecznemu? - Bartosiewicz, Stanisława (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
General recognition of the doctrine of neoliberalism, which resulted are flexible forms of work, create a new social class precariat. At the turn of the XX and XXI century there was a lot of scientific literature on this topic. Some scholarly economists, sociologists, social psychologists express the opinion that precariat is the class which threatens social stability just as the proletariat, which in the nineteenth century and the first half of the twentieth century, won for himself a few types of labour security, which rights deprived from precariat. The author of paper shows the opposite view on the current position of precariat. She considers that precariat isn’t a class with regard for a fight between its subgroups. Not being a class doesn’t have enough strength to fight for the improvement of his being. Now, there isn’t a dangerous class
Mathematical Economics, 2016, Nr 12 (19), s. 83-90
Keywords: precariat; labor market; social groups; neoliberalism